Towards an ethnography of sensible modalities of knowing in care activities - Fabienne Malbois; Alexandre Lambelet (Revue d'anthropologie des connaissances)
This introductory article shows how knowing in care activities is developed in sensible experience, and takes the form of understanding of situations. It begins by specifying the type of epistemological positioning that socio-anthropological knowledge must adopt in order to be able to grasp practical knowledge in care. After situating the issue of sensible knowledge within works on the senses and, emphasising the importance of considering the sensible as know-how, it presents two modes of knowledge which elude representational theories of knowing, and therefore diverge from a purely cognitive conception of knowledge: expertise (based on the evidential paradigm), and inquiry (based on the experience paradigm). Finally, it shows how these two modes of knowing are being profoundly reworked by ethnographies looking at a variety of care activities.